Coordination and Activation of AlH and GaH Bonds. Issue 52 (30th October 2014) - Abdalla, Joseph A. B.; Riddlestone, Ian M.; Turner, Joshua; Kaufman, Paul A.; Tirfoin, Remi; Phillips, Nicholas; Aldridge, Simon
Abstract The modes of interaction of donor‐stabilized Group 13 hydrides (E=Al, Ga) were investigated towards 14‐ and 16‐electron transition‐metal fragments. More electron‐rich N‐heterocyclic carbene‐stabilized alanes/gallanes of the type NHC⋅EH3 (E=Al or Ga) exclusively generate κ2 complexes of the type [M(CO)4(κ2‐H3E⋅NHC)] with [M(CO)4(COD)] (M=Cr, Mo), including the first κ2 σ‐gallane complexes. β‐Diketiminato (′nacnac′)‐stabilized systems, HC(MeCNDipp)2EH2, show more diverse reactivity towards Group 6 carbonyl reagents. For HC(MeCNDipp)2AlH2, both κ1 and κ2 complexes were isolated, while [Cr(CO)4(κ2‐H2Ga(NDippCMe)2CH)] is the only simple κ2 adduct of the nacnac‐stabilized gallane which can be trapped, albeit as a co‐crystallite with the (dehydrogenated) gallylene system [Cr(CO)5(Ga(NDippCMe)2CH)]. Reaction of [Co2(CO)8] with HC(MeCDippN)2AlH2 generates [(OC)3Co(μ‐H)2Al(NdippCme)2CH][Co(CO)4] (12), which while retaining direct AlH interactions, features a hitherto unprecedented degree of bond activation in a σ‐alane complex.